KONTRIBUSI WANITA TANI DALAM KEGIATAN PASCA PANEN PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Sukmawati Abdullah (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The contribution of women farmers in post-harvest rice activities in Baruga is substantial and plays an important role in improving quality, economic value, and food security. However, this contribution is often underappreciated, and these farmers face various structural obstacles. Therefore, there is a need for capacity building and more adequate support. The objective of this study is to provide a comprehensive account of the contributions of women farmers in post-harvest activities in rice farming in Baruga Village, Baruga District, Kendari City. The population under study comprised female farmers from Baruga Village who cultivated rice in 2025, with a total sample size of 122 individuals. The sample was selected using simple random sampling. The total number of research subjects was 24 female farmers. The research variable was the contribution of female farmers to post-harvest activities for rice. The data presented herein were collected through the implementation of in-person interviews, which were conducted using a structured questionnaire. Furthermore, observation and documentation methods were employed to substantiate the research findings. The research data were analyzed using descriptive statistics. A multifaceted approach was employed to analyze the post-harvest rice activities, entailing the utilization of both descriptive statistics and class interval formulas to elucidate the variables involved. The findings indicated that the contribution of women farmers to post-harvest rice activities, encompassing transportation, drying, storage, and cleaning, was classified as high-impact. In contrast, threshing was categorized as medium-impact, and milling was designated as low-impact. The level of contribution of women farmers in post-harvest activities in rice farming in Baruga Village, Baruga District, was found to be in the high category, with a total of 10 people or 41.67 percent.